How iron ore pellets are made

The de-crystallization and controlled processing of low-grade iron ores address the issues of strength and explosion risk in pellet manufacturing, resulting in stable and high-yield iron ore pellets.

JP7626241B2Active Publication Date: 2025-02-04JFE STEEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023552600
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-05-10
Publication Date
2025-02-04
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

Existing methods for manufacturing iron ore pellets using low-grade ores with high crystalline content face challenges in controlling pellet strength and suppressing explosion or powdering during the baking process, due to inadequate processing temperatures and times, leading to instability and reduced yield.

Method used

A method involving a de-crystallization process to remove crystalline crystals from iron ore, followed by controlled heating, crushing, and granulation to achieve a specific particle size distribution, ensuring the pellets have sufficient strength and reduced explosion risk.

Benefits of technology

The method balances pellet strength and explosion suppression, achieving high-quality iron ore pellets with improved stability and yield by maintaining appropriate processing temperatures and times, and controlling particle size distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626241000004
    Figure 0007626241000004
  • Figure 0007626241000005
    Figure 0007626241000005
  • Figure 0007626241000001
    Figure 0007626241000001
Patent Text Reader

Abstract

Provided is an iron ore pellet production method with which both suppression of bursting and strength of an iron ore pellet are achieved. This iron ore pellet production method involves a crystalline water removal treatment step for eliminating crystalline water from iron ore having an iron content ratio of 63% by mass or less to obtain dewatered ore, wherein iron ore in a state of being heated to 100°C-800°C is kept for 5-200 minutes in the crystalline water removal treatment step.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing iron ore pellets. [Background technology]

[0002] In reduction using the shaft furnace method, which is currently the mainstream direct reduction ironmaking method, lump ore or pellets are used as the charging raw materials. Pellets are manufactured through the processes of crushing, mixing, granulating, and firing the ore. In this manufacturing process, iron ore pellets before firing (so-called green pellets) are required to have a strength sufficient to prevent them from crumbling or powdering during handling, such as transportation from the granulation process to the firing process.

[0003] In order to control the strength of green pellets, it is important to control the particle size of the ore powder after crushing, and it is known that the strength of green pellets increases as the ratio of fine powder increases. Also, it is known that in the firing process, the moisture in the green pellets evaporates, causing a phenomenon called bursting, in which the green pellets explode or break into powder, resulting in a decrease in yield.

[0004] For example, JP-A-04-099132 (Patent Document 1) discloses a method for producing pellets from iron ore containing a large amount of water of crystallization. In this production method, raw iron ore containing a large amount of water of crystallization is crushed and granulated, and then the steps of drying, dewatering, and preheating are followed by an additional firing step to produce fired pellets. Before crushing a part or all of the raw iron ore, at least a part of the water of crystallization in the raw iron ore is dewatered in advance. This production method is said to realize a reduction in bursting and an improvement in product yield due to an increase in the crushing strength of the preheated pellets. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 04-099132 Summary of the Invention [Problem to be solved by the invention]

[0006] Currently, high-grade ore with little water of crystallization is generally used as the raw material for pellets (iron ore). However, as demand for high-grade ore increases in the future, it is predicted that it will become more difficult to secure a stable supply of high-grade ore. For this reason, the use of low-grade ore with an iron content (total Fe content) of 63 mass% or less, produced in Australia, India, etc., is being considered. When the amount of water of crystallization in iron ore pellets (green pellets) increases, they become more prone to bursting as mentioned above, so there is a need to improve the manufacturing method for pellets to suppress bursting.

[0007] In the pellet manufacturing method of Patent Document 1, it is considered that the water of crystallization cannot be appropriately reduced unless the ore is subjected to a dehydration treatment at an appropriate treatment temperature and time. However, such appropriate treatment temperature and time are not taken into consideration in the pellet manufacturing method of Patent Document 1. Furthermore, excessive dehydration treatment deteriorates the crushability of the ore, making it difficult to control the particle size to an appropriate size in the crushing process, and may make it difficult to ensure the strength of the iron ore pellets. Therefore, it is desired to provide a manufacturing method of iron ore pellets that can achieve both suppression of bursting and strength of the iron ore pellets.

[0008] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a method for producing iron ore pellets that achieves both suppression of bursting and strength of the iron ore pellets. [Means for solving the problem]

[0009] In order to achieve the above object, the method for producing iron ore pellets according to the present disclosure is as follows.

[0010] [1] A dehydration treatment step of removing hydration water from iron ore having an iron content of 63% by mass or less to obtain dehydrated ore, In the crystallization water removing treatment step, the iron ore is heated to 100° C. or more and 800° C. or less and kept at that temperature for 5 minutes or more and 200 minutes or less.

[0011] The method for producing iron ore pellets according to the present disclosure may further be as follows.

[0012] [2] The method further comprises a grinding step of grinding the dehydrated ore to obtain ore powder; The method for producing iron ore pellets according to the above [1], wherein the proportion of the ore powder having a particle diameter of 10 μm or less as determined by sieving is 10% by mass or more and 70% by mass or less.

[0013] [3] The method for producing iron ore pellets according to [2] above, wherein the proportion of the particle diameter of 10 μm or less is 25 mass% or more and 60 mass% or less.

[0014] [4] The method for producing iron ore pellets according to [2] or [3] above, wherein the proportion of the particle diameter of 10 μm or less is 25 mass% or more and 60 mass% or less.

[0015] [5] The method for producing iron ore pellets according to any one of [1] to [4] above, wherein the content of water of crystallization in the iron ore is 3.0 mass% or more. Effect of the Invention

[0016] According to the method for producing iron ore pellets disclosed herein, it is possible to provide a method for producing iron ore pellets that achieves both suppression of bursting and strength of the iron ore pellets. [Brief description of the drawings]

[0017] [Figure 1] 1 is a graph showing the relationship between the strength of green pellets and the proportion of particles with a particle diameter of 10 μm or less in the ore powder. [Diagram 2] 1 is a graph showing the relationship between the passing rate of pellet fragments of green pellets and the rate of particle diameters of 10 μm or less in the ore powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] A method for producing iron ore pellets according to an embodiment of the present disclosure will be described.

[0019] First, an overview of the manufacturing method of iron ore pellets according to the present embodiment will be described. The iron ore pellets according to the present embodiment are so-called green pellets (pellets before firing). The manufacturing method of iron ore pellets according to the present embodiment includes a dehydration process step in which crystallization water is removed from iron ore having an iron content of 63 mass% or less (so-called low-grade ore) to obtain dehydrated ore. In the following description, iron ore having an iron content of 63 mass% or less will be simply referred to as iron ore.

[0020] In the crystallization water removal treatment process, the iron ore is heated to 100°C or more and 800°C or less and held at that temperature for 5 minutes or more and 200 minutes or less.

[0021] The method for producing iron ore pellets may further include a crushing step of crushing the dehydrated ore to obtain ore powder. In the crushing step, the ore powder is crushed so that the ratio of particles having a particle diameter of 10 μm or less is 10% by mass to 70% by mass.

[0022] According to the method for producing iron ore pellets according to this embodiment, it is possible to suppress bursting while maintaining the strength of the iron ore pellets.

[0023] Bursting is a phenomenon in which iron ore pellets (green pellets) explode or break into powder when heated due to the water content in the pellets evaporating.

[0024] The method for producing iron ore pellets according to this embodiment will be described in detail below.

[0025] The manufacturing method of iron ore pellets according to the present embodiment may further include a granulation step in which the ore powder is granulated to obtain iron ore pellets (green pellets) in addition to the above-mentioned decrystallization water treatment step and pulverization step. The green pellets may then be fired in a firing step to obtain fired pellets. In the following description, in order to distinguish between pellets before and after firing, the iron ore pellets according to the present embodiment (pellets before firing) may be referred to as green pellets, and the pellets after firing may be referred to as fired pellets. The green pellets and fired pellets may contain raw materials other than iron ore (e.g., bentonite).

[0026] The type and composition (ore composition) of the iron ore used as the raw material for the green pellets are not particularly limited. The raw material for the green pellets may consist of a single iron ore or may be a mixture of multiple ores in any composition.

[0027] The content of water of crystallization in the iron ore (before the water of crystallization process) that is the raw material for the green pellets is not particularly limited. The content of water of crystallization can be measured as the weight loss of the iron ore (LOI: Loss On Ignition) when the iron ore is held at 1000°C for 30 minutes.

[0028] The water of crystallization removal process is a process for removing water of crystallization from iron ore to obtain dehydrated ore. In the water of crystallization removal process, the iron ore is heated to remove water of crystallization from the iron ore.

[0029] In the dewatering process, the iron ore is heated and held at a dewatering temperature of 100°C or more and 800°C or less. In this dewatering process, the holding time for holding the iron ore at the temperature in the above temperature range (hereinafter referred to as dewatering time) is 5 minutes or more and 200 minutes or less. If the dewatering time is less than 5 minutes, the water of crystallization may not be sufficiently removed from the iron ore. If the dewatering time is longer than 200 minutes, the crushability of the iron ore may deteriorate. In these cases, the strength of the green pellets may decrease. Therefore, the dewatering time is set to 5 minutes or more and 200 minutes or less.

[0030] The time for removing water of crystallization is preferably 180 minutes or less. When the time for removing water of crystallization is 180 minutes or less, a decrease in strength of the green pellets can be appropriately avoided.

[0031] In the crystallization water removal process, the crystallization water removal temperature and the crystallization water removal time are important factors for removing the crystallization water. If the crystallization water removal temperature is less than 100°C, the crystallization water cannot be sufficiently removed from the iron ore. If the crystallization water removal temperature is higher than 800°C, the crushability of the iron ore deteriorates, and the strength of the green pellets is insufficient. Therefore, the crystallization water removal temperature is set to 100°C or higher and 800°C or lower. If the crystallization water removal temperature is within this range and the crystallization water removal time is 5 minutes or higher and 200 minutes or lower as described above, it is possible to achieve both suppression of bursting and strength of the green pellets.

[0032] The temperature for removing the water of crystallization is preferably 200° C. or more and 500° C. or less. When the temperature for removing the water of crystallization is within this range, the strength of the green pellets can be sufficiently increased. In addition, bursting can be suppressed more effectively.

[0033] The content of crystal water in the dehydrated ore is not particularly limited. The content of crystal water in the dehydrated ore can be measured as LOI in the same manner as the content of crystal water in the iron ore before the crystal water removal process. The content of crystal water in the dehydrated ore is preferably reduced by 10% by mass or more from the content of crystal water in the iron ore before the crystal water removal process.

[0034] The crushing step is a step of crushing the dehydrated ore to obtain ore powder. In this embodiment, the crushing method of the dehydrated ore in the crushing step and the crushing time required for crushing are not particularly limited. When crushing the dehydrated ore by batch processing, the crushing time is preferably 15 minutes or more and 75 minutes or less.

[0035] The shape of the ore powder is not particularly limited. The particle size of the ore powder is preferably, for example, 95 mass % or more of particles having a diameter of 300 μm or less.

[0036] The particle size distribution of the ore powder is preferably such that the ratio of particles with a particle diameter of 10 μm or less is 10% by mass or more and 70% by mass or less. The particle size or particle size distribution of the ore powder is an important factor that affects the strength of the green pellets. The ore powder can be obtained by crushing iron ore. The method of crushing the iron ore is not particularly limited.

[0037] In the particle size distribution of the ore powder, the proportion of fine powder with a particle size of 10 μm or less has a large effect on the strength of the green pellets. If the proportion of fine powder with a particle size of 10 μm or less in the particle size distribution of the ore powder is less than 10 mass%, green pellets with sufficient strength may not be obtained.

[0038] The reason why bursting may not be suppressed when the proportion of fine powder with a particle diameter of 10 μm or less is more than 70 mass% in the particle size distribution of the ore powder is not clear. However, for example, the following reason is predicted. That is, when the proportion of fine powder is excessive in the particle size distribution of the ore powder, the structure of the green pellet becomes dense. Therefore, the diffusion path (flow path leading from the inside of the green pellet to the outside of the pellet) of the crystal water desorbed by heating during sintering is reduced. As a result, the pressure inside the green pellet is likely to increase due to the water vaporized inside the green pellet. Therefore, it is considered that bursting may not be suppressed when the proportion of fine powder with a particle diameter of 10 μm or less is more than 70 mass% in the particle size distribution of the ore powder.

[0039] In the particle size distribution of the ore powder, the ratio of fine powder having a particle size of 10 μm or less is preferably 20% by mass to 60% by mass, which makes it possible to suppress bursting while obtaining an appropriate strength of the green pellets.

[0040] The granulation process is a process of granulating the ore powder to obtain iron ore pellets (green pellets). The granulation method in the granulation process is not limited. In the granulation process, for example, the ore powder may be granulated using a pelletizer. As the pelletizer, for example, a pan-type granulator (so-called pan pelletizer) may be used.

[0041] In this embodiment, the shape and size (e.g., particle size and average particle size) of the iron ore pellets are not particularly limited and may be any value. The size of the green pellets may be evaluated, for example, by measuring the major axis diameter and minor axis diameter using a caliper and averaging the measurements as the particle size of the green pellets. The particle size of the green pellets is preferably 9 mm to 16 mm, which is commonly used in this technical field.

[0042] The green pellets are then subjected to a firing process to be fired into fired pellets at a firing temperature of, for example, 1200°C to 1350°C.

[0043] In the method for producing iron ore pellets according to the present embodiment, when the temperature for removing the water of crystallization and the time for removing the water of crystallization are within the above-mentioned ranges, the green pellets have a strength generally required in the technical field (for example, 1.0 kg / pellet or more). The strength of the green pellets is preferably 1.0 kg / pellet or more. In the method for producing iron ore pellets according to the present embodiment, the strength of the green pellets tends to be higher when the particle size distribution of the raw material ore powder is a predetermined distribution, that is, when the proportion of particles with a particle diameter of 10 μm or less is 10 mass% or more and 70 mass% or less. The strength of the green pellets can be measured by the method described in the examples described later.

[0044] In the method for producing iron ore pellets according to the present embodiment, bursting can be suppressed if the temperature and time for removing water of crystallization are within the above-mentioned ranges. In the method for producing iron ore pellets according to the present embodiment, bursting can be suppressed more effectively if the particle size distribution of the raw material ore powder is the above-mentioned predetermined distribution.

[0045] Now, as described above, bursting is a phenomenon in which the green pellet explodes or breaks into powder when the green pellet is heated, due to the evaporation of moisture in the green pellet. The likelihood of bursting, i.e., bursting property, can be evaluated based on the ratio of pellets of 5 mm or less generated after the green pellet is heated at a predetermined temperature (e.g., 300°C) or after the green pellet is fired. In detail, if bursting occurs during the firing process or when the green pellet is heated at a predetermined temperature (hereinafter referred to as the firing process, etc.), the green pellet explodes or breaks into powder, generating fine pellet pieces (e.g., 5 mm or less). Therefore, if the amount of pellet pieces generated during the firing process, etc. is large, bursting is likely to occur (high bursting property), and it can be evaluated as not being good from the viewpoint of suppressing bursting. Conversely, if the amount of pellet pieces generated during the firing process, etc. is small, bursting is unlikely to occur (low bursting property), and it can be evaluated as being good from the viewpoint of suppressing bursting.

[0046] If the amount of pellet fragments generated during the firing process etc. is 3.0 mass % or less, preferably 1.5 mass % or less, and more preferably 1.0 mass % or less, a decrease in the yield of fired pellets can be suppressed. Therefore, if the amount of pellet fragments generated during the firing process etc. is 1.0 mass % or less, it can be evaluated as a good quality green pellet in which bursting is suppressed. EXAMPLES

[0047] Green pellets were produced according to the following procedure, and the bursting properties were evaluated.

[0048] As the iron ore (raw ore) used as the raw material for the green pellets, ores (Ore A, Ore B) having the chemical composition shown in Table 1 were used. As described above, "LOI" in Table 1 indicates the content (mass%) of crystal water. In addition, in Table 1, "T.Fe" indicates the mass% of the iron content (total Fe content) in the iron ore. Note that "T.Fe" is a value quantified based on the total iron quantification method for iron ore specified in JIS M 8212:2022. As shown in Table 1, both Ore A and Ore B used as raw materials for the green pellets are iron ores with T.Fe of 63 mass% or less (so-called low-grade ores).

[0049] [Table 1]

[0050] Table 2 shows information on the ore used for the green pellets (ore properties) and the conditions or evaluation results of the crystallization water removal treatment process, crushing process, granulation process, and firing process. In the following, the ore blends shown in Table 2 were used to obtain green pellets of Experiments No. 1 to 16 through the crystallization water removal treatment process, crushing process, granulation process, and firing process described below.

[0051] [Table 2]

[0052] Each raw ore was mixed in the ore blending ratio shown in Table 2, and dehydrated ore was obtained by dehydration treatment at the temperature and time shown in Table 2 (dehydration step). The dehydration treatment was carried out in the air. The LOI of the dehydrated ore is shown in Table 2 as the content of water of crystallization of the dehydrated ore.

[0053] Next, the dehydrated ore was pulverized (batch processing) in a ball mill for the pulverization time shown in Table 2 to obtain ore powder (pulverization process). The proportion of fine powder with a particle size of 10 μm or less in the ore powder was then measured as the passing rate (mass %) through a sieve with a mesh size of 10 μm in sieving. In Table 2, the proportion of fine powder with a particle size of 10 μm or less in the ore powder is shown as the "-10 μm proportion" in the pulverization process.

[0054] Table 3 shows the cumulative 10% diameter (D10), cumulative 50% diameter (D50: median diameter), and cumulative 90% diameter (D90) on a volume basis as the particle size distribution of the ore powder. These cumulative 10% diameter, cumulative 50% diameter, and cumulative 90% diameter were derived based on the volume-based particle size distribution of the ore powder measured using a laser diffraction particle size measurement (Malvern, Mastersizer 3000). The dispersion medium used in measuring the particle size distribution is water. For ease of reference, Table 3 lists the same "-10 μm ratio" as shown in Table 2 again.

[0055] [Table 3]

[0056] Next, 1.0% by mass of bentonite was added to the ore powder to obtain a mixed powder. Although bentonite was added as a binder during granulation, it is not essential in this embodiment. This mixed powder was granulated using a pan-type granulator (pelletizer) to obtain green pellets (granulation process). During granulation, the mixed powder was rolled while adding water so that the granulation moisture (amount of water added) was 10% to 10.5% by mass of the weight of the green pellets. The granulation moisture can be determined by measuring the weight change before and after holding the green pellets at 105°C for 24 hours. For example, if the weight change rate after holding the green pellets at 105°C for 24 hours is minus 10% by weight, the granulation moisture is 10%.

[0057] The particle size of the green pellets was determined by measuring the major and minor axis diameters with a vernier caliper and taking the average value (arithmetic mean). For each green pellet of each experiment number, the particle size of 10 pellets was measured and the average value (arithmetic mean) was used as the particle size of the green pellets of that experiment number.

[0058] The strength of the green pellets was measured using an autograph. The strength of the green pellets was measured by deforming the green pellets at a displacement speed of 1 mm / min to obtain a load-displacement curve. The load corresponding to the first peak position of displacement in the load-displacement curve was used as the strength of the green pellets. For each green pellet in each experiment number, the strength of 10 pellets was measured, and the average value (arithmetic mean) was used as the strength of the green pellets in that experiment number.

[0059] The bursting property was evaluated based on the amount of pellet pieces generated after the firing process. Specifically, the bursting property was evaluated as follows. First, 500 g of green pellets were charged into a vertical furnace (cylindrical shape with a diameter of 60 mm), and 300°C air was passed from below the layer of green pellets to above at a wind speed of 1.0 m / sec (however, converted to 300°C / 1 atmosphere) for 10 minutes. Next, the green pellets after being exposed to the 300°C air were heated to 1250°C in an electric furnace other than the above furnace, and fired at this temperature for 25 minutes (firing process). Thereafter, the green pellets were taken out of the furnace and sieved through a sieve with a mesh size of 5 mm, and the passing ratio (mass%) of the pellet pieces that passed through the sieve was measured to evaluate the bursting property. In Table 2, the passing ratio of the pellet pieces is shown as "-5 mm ratio".

[0060] As shown in Table 2, the green pellets of Experiments 1 to 5, 8 to 14, 17 and 18, in which the crystallization water removal temperature was 100°C or higher and 800°C or lower and the crystallization water removal time was 5 minutes or higher and 200 minutes or lower, had a strength of 1.0 kg / pellet or higher. In addition, the green pellets of these Experiments had a passing rate of pellet pieces (-5 mm rate), which is an index of bursting property, of 3.0 mass% or lower, specifically 1.5 mass% or lower. In other words, the green pellets of these Experiments according to this embodiment have both strength and bursting property.

[0061] In the manufacturing process of green pellets in Experiments Nos. 1 to 5, 8 to 14, 17, and 18, the content of water of crystallization in the dehydrated ore (LOI of the dehydrated ore) is reduced by 14% by mass or more from the content of water of crystallization in the iron ore (raw ore) before the water of crystallization process (LOI of the raw ore) in the water of crystallization treatment process. Compared with Experiments Nos. 6 and 15, which do not achieve both strength and bursting property of the green pellets, it is considered preferable that the content of water of crystallization in the dehydrated ore is reduced by 10% by mass or more from the content of water of crystallization in the iron ore before the water of crystallization process.

[0062] As shown by the green pellets of Experiments No. 1 to 5, 8 to 14, 17 and 18, even if the content of water of crystallization in the iron ore before the dewatering process is 4.9% by mass or more, it is possible to achieve both strength and bursting properties of the green pellets. Therefore, if the content of water of crystallization in the iron ore before the dewatering process is less than 4.9% by mass, for example, 3.0% by mass or more, it is considered that the strength and bursting properties of the green pellets can be achieved at the same time if the dewatering process temperature is 100°C or more and 800°C or less, and the dewatering time is 5 minutes or more and 200 minutes or less. In addition, in the high-grade ore used in the conventional direct reduction ironmaking process, the content of water of crystallization is almost always around 1.0% by mass or less. In addition, in the iron ore pellets for blast furnaces, iron ore with a content of water of crystallization of less than 3.0% by mass at most (maximum) is used.

[0063] Furthermore, among the green pellets of Experiments Nos. 1 to 5, 8 to 14, 17, and 18, the green pellets of Experiments Nos. 1 to 5, 10 to 14, 17, and 18, in which the ratio of particles with a diameter of 10 μm or less (-10 μm ratio) in the ore powder was 10% by mass or more and 70% by mass or less, had a passing ratio of pellet pieces (-5 mm ratio), which is an index of bursting properties, of 1.0% by mass or less, and were particularly good. Furthermore, the green pellets of these Experiments Nos. 8 and 9, in which the ratio of particles with a diameter of 10 μm or less (-10 μm ratio) in the ore powder was not 10% by mass or more and 70% by mass or less, were also good in terms of the strength of the green pellets.

[0064] In addition, when comparing the green pellets of Experiments Nos. 1 to 5, 10 to 14, 17 and 18 with the green pellets of Experiments Nos. 8 and 9, it can be seen that if D90 is 50 μm or more and 200 μm or less, the strength of the green pellets tends to be high.

[0065] In addition, the green pellets in Experiments 6 and 7, in which the crystallization water removal temperature was from 100° C. to 800° C., and the green pellets in Experiments 15 and 16, in which the crystallization water removal time was from 5 minutes to 200 minutes, had a strength of less than 1.0 kg / pellet or a passing rate of pellet pieces (-5 mm rate) of more than 1.0 mass%. In other words, the green pellets in Experiments 6, 7, 15, and 16 did not have both strength and bursting properties.

[0066] Figure 1 shows the relationship between the strength of the green pellets and the proportion of the ore powder with a particle diameter of 10 μm or less (-10 μm proportion) in Experiments Nos. 1 to 5, 8 to 14, 17, and 18. Figure 2 shows the relationship between the passing fraction of pellet fragments (-5 mm fraction) of the green pellets and the proportion of the ore powder with a particle diameter of 10 μm or less (-10 μm fraction) in Experiments Nos. 1 to 5, 8 to 14, 17, and 18.

[0067] According to the graph shown in Figure 1, it can be seen that when the proportion of particles with a diameter of 10 μm or less in the ore powder (-10 μm proportion) is 10% by mass or more and 70% by mass or less, the strength of the green pellets is 1.0 kg / pellet or more. In particular, it can be seen that the strength of the green pellets is higher when the proportion of particles with a diameter of 10 μm or less in the ore powder is 25% by mass or more and 60% by mass or less. As shown by the solid line in Figure 1, the strength of the green pellets generally becomes convex upward as the proportion of particles with a diameter of 10 μm or less in the ore powder moves from the small side to the large side.

[0068] According to the graph in Fig. 2, when the proportion of the ore powder with a particle diameter of 10 μm or less (-10 μm proportion) is 10 mass% or more and 70 mass% or less, the passing proportion of pellet fragments (-5 mm proportion) is 1 mass% or less. As shown by the dashed line in Fig. 2, as the proportion of the ore powder with a particle diameter of 10 μm or less moves from the small side to the large side, the passing proportion of pellet fragments generally becomes downward convex.

[0069] Comparing the graphs in Figures 1 and 2, it can be said that, overall, it is particularly preferable when the proportion of particle diameters of 10 μm or less (-10 μm proportion) in the ore powder is 25% by mass or more and 60% by mass or less, because the pellet strength is particularly high and the passing proportion of pellet pieces is stably low, thereby effectively suppressing bursting.

[0070] In this manner, a method for producing iron ore pellets can be provided.

[0071] Note that the embodiments disclosed in this specification are merely examples, and the embodiments of the present disclosure are not limited thereto, and may be modified as appropriate within the scope of the purpose of the present disclosure. [Industrial Applicability]

[0072] The present disclosure is applicable to methods for producing iron ore pellets.

Claims

1. a dehydration treatment step of removing water of crystallization from iron ore having an iron content of 63% by mass or less to obtain dehydrated ore; A grinding step of grinding the dehydrated ore to obtain ore powder, In the crystallization water removal treatment step, the iron ore is heated to 100° C. or more and 800° C. or less for 5 minutes to 200 minutes, The method for producing iron ore pellets, wherein the ore powder has a particle diameter of 10 μm or less of 10 mass % or more and 70 mass % or less as determined by sieving.

2. The method for producing iron ore pellets according to claim 1, wherein the proportion of the particle diameter of 10 μm or less is 25 mass% or more and 60 mass% or less.

3. The method for producing iron ore pellets according to claim 2, wherein the ore powder has a cumulative 90% diameter in a volume-based particle size distribution of 50 μm or more and 200 μm or less.

4. The method for producing iron ore pellets according to any one of claims 1 to 3, wherein the content of water of crystallization in the iron ore is 3.0 mass% or more.

Citation Information

Patent Citations

  • Production of pellet of iron ore containing much water of crystallization

    JP1992099132A

  • Method for producing iron-ore pellet

    JP2010163656A

  • Sintered pellet production device

    JP2017031444A